Reprodução de Meloidogyne incognita, M. javanica e Pratylenchus coffeae em Diferentes Cultivares de Bananeira - de Jesus, Alniusa Maria; Wilcken, Silvia Renata Siciliano [UNESP] (My University, 2010)
Banana (Musa spp.) is one of the most consumed fruits in the world, and it is cultivated in many tropical countries. In Brazil, the productivity is low due to several factors such as the incidence of pests and diseases. The nematodes are among the most important problems found in the production of bananas. This research studied the reproduction of Meloidogyne incognita race 2, M. javanica and Pratylenchus coffeae in different cultivars of banana. The evaluation of the experiments with Meloidogyne spp. was carried out 120 days after the inoculation. The analyzed parameters were: number of gall, number of the external masses of eggs, number of eggs per gram of root, reproduction factor and number of juveniles in the soil. The evaluation of the experiment with P. coffeae was carried out 90 days after the inoculation; the final population was evaluated. The cultivars PV-0344, Maca, Grande Naine, FHIA 01, Thap Maeo and Prata Ana allowed greater multiplication of P. coffeae than Caipira, SH-3640 and FHIA-18. For M. javanica, the cultivars Calypso, Bucanneer, Grande Naine, PV-0344, Nanicao Magario, FHIA-02, SH-3640, Pacovan, and Prata Ana exhibited larger populations, decreasing in Maca. All cultivars allowed high multiplication rates of M. incognita.
Reproduction of Meloidogyne incognita, M. javanica and Pratylenchus coffeae in banana.